Midgut malrotation and volvulus presenting outside of the newborn period - Brian D. Skidmore, M.D; Michael C. Larson, M.D., Ph.D; Sarah M. Desoky, M.D; Dorothy Gilbertson-Dahdal, M.D (Elsevier, 2022)
Intestinal malrotation with midgut volvulus is a commonly considered differential diagnosis in the neonate or infant with bilious emesis and abdominal pain. The classically-taught scenario in which midgut volvulus occurs is in the neonate with bilious emesis [1]. This teaching, however, is being challenged. Recent data of over 60,000 pediatric hospitalizations demonstrated that only approximately 30% of pediatric discharges for malrotation were 1 month old or less, and that 42% of those with malrotation as a discharge diagnosis were older than 1 year. Indeed, only 75% of cases cumulatively presented before 5 years of age [2]. This discordance in perception of age and reported age of presentation results in malrotation being lower on, or even excluded from, the differential diagnosis when older infants or children present with emesis and abdominal pain. Thus, the consideration of midgut malrotation and volvulus should not be dismissed in any pediatric patient with bilious or repeated emesis and abdominal pain. This pictorial essay reviews cases of midgut malrotation and volvulus presenting outside of the typical newborn period with studies from various modalities, and is intended to raise awareness of late-presenting midgut volvulus.